BOARD SIZE, BOARD COMPOSITION, LEVERAGE AND ITS EFFECT ON INTELLECTUAL CAPITAL DISCLOSURE - Nariman, Augustpaosa; Hastuti, Rini Tri; Prajogi, M. Bintang (Graduate Program of Universitas Tarumanagara, 2023)
Disclosure of non-financial information by companies is very important information, such as voluntary disclosures. The most common type of information used by investors is not actually disclosed by managers in annual reports. This causes a social gap between investors and management. It can be concluded from the research that voluntary disclosure is very important to improve the quality of annual reports and satisfy the interests of stakeholders. A management system that can work professionally, honestly and transparently can increase demand from the market and will encourage companies to provide more transparent information. The information disclosed in the financial statements is actually not able to represent the overall condition of the company in order to produce values and make decisions by investors. Therefore, in order to increase value and assist investors in making decisions, companies can disclose information voluntarily. With this obligation, it can encourage companies to disclose more information, because honesty and transparency are the basis of corporate governance, this is what is referred to as disclosure of intellectual capital (intellectual capital disclosure) The main purpose of this research is to find empirical proof about the effect of board size, board composition, and leverage on intellectual capital disclosure. The data used in this research were obtained from manufacturing companies that listed on the Indonesian Stock Exchange (IDX). 288 data were gathered from 144 companies in the year of 2020-2021. Purposive sampling method is used to collect the data and panel data regression model is used for hypothesis testing. Software EViews 9 is used for preparing and processing data. This research reached a conclusion that the number of board composition is positive and have not give a significant effect on intellectual capital disclosure. Variables of board size and leverage have a negative and dont have a significant effect on intellectual capital disclosure.